The Political Economy of Embedded Marketing in the Television Quiz Show Family 100: A Qualitative Study - Windy Masyitoh; Indra Prawira (Sekolah Tinggi Agama Islam Kuningan, 2026)
Background: The television quiz show Family 100, broadcast on MNCTV, demonstrates the integration of commercial interests into family entertainment programming through prize-based promotional practices. Objective: This study aimed to examine the commodification of prizes as a form of embedded advertising and its implications for media economics and consumer culture. Methods: This qualitative study employed semi-structured interviews with producers, members of MNCTV’s creative team, and sponsors. The data were analyzed through data reduction, data display, and conclusion drawing and verification. The validity of the findings was established through source, methodological, and theoretical triangulation. Results: The findings revealed three forms of commodification: content commodification through the integration of sponsored prizes into program narratives; labor commodification through creative processes shaped by commercial interests; and audience commodification through the transformation of viewers’ attention into a marketable asset for advertisers. Conclusion: The Family 100 program functioned not only as a form of entertainment but also as an economic space that reflected media capitalism through the symbolism of prizes and family-oriented narratives. The study underscores the importance of transparent disclosure of sponsored content by media practitioners and the establishment of clearer regulations governing embedded advertising by broadcasting authorities. Future research should examine audience reception, compare commodification practices across television genres, and investigate their transformation amid the convergence of television and digital media platforms.